The role of nintedanib and pirfenidone in the treatment of idiopathic pulmonary fibrosis and review of recent clinical trials of IPF therapy - Żuber, Michał; Dąbrowska, Paulina; Dacka, Michał (Quality in Sport, 2024)
Idiopathic pulmonary fibrosis (IPF) is a chronic, rare disease characterized by continuous fibrosis of the lung parenchyma. It mainly affects the elderly; however, it is increasingly being diagnosed in younger patients as well. Risk factors include smoking, occupational dust exposure and genetic factors. Symptoms of IPF include shortness of breath, dry cough and reduced exercise tolerance, leading to a reduced quality of life for patients. Diagnosis is based on imaging, mainly high-resolution CT scans, and the exclusion of other causes of interstitial lung disease. Two antifibrotic drugs, nintedanib and pirfenidone, are now approved to slow disease progression. Nintedanib acts as a tyrosine kinase inhibitor, blocking the signaling pathways of lung fibroblasts. Pirfenidone, on the other hand, has anti-inflammatory and anti-fibrotic effects by inhibiting TGF-b signaling pathways. Clinical trials have confirmed their efficacy in reducing the decline in increased vital capacity and the risk of disease progression. In Poland, patients with IPF can benefit from nintedanib and pirfenidone therapy under the drug program. Despite advances in treatment, more research is needed on new IPF therapies. Clinical trials of zinpentraxin, ziritaxestat and pambrevalumab have not confirmed their efficacy in treating IPF. Results from initial studies of bexotegrast show promise, but further studies are needed and are ongoing. Despite advances in the treatment of IPF, further research into new therapies is needed to improve therapeutic outcomes and patient quality of life.